INTERPERSONAL COMMUNICATION IN THE QUR'AN: ANALYSIS OF THE STORIES OF THE PROPHETS - Ulvah Nur'aeni; Nurul Afrianti; Fitroh Hayati; Kasimah binti Kamaruddin (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2025)
This article focuses on outlining the moral messages behind the various forms of interpersonal communication in the Quran. This is motivated by the current phenomenon in which communication has been dominated by technological advancements and social media that offer convenience. While communication through social media brings great benefits to life, it is still unable to fully represent a persons feelings and emotions. Talking or discussing through social media has now shifted face-to-face communication. Face-to-face communication has become something unfamiliar and missed by some people. Therefore, this article aims to highlight once again the urgency of interpersonal or face-to-face communication in accordance with the guidance of the Quran. Based on an exploration of the Quranic verses regarding interpersonal communication, six themes are recorded in the Quran. These themes reflect a variety of communication contexts, providing guidance for interacting in every situation and with every interlocutor. This study uses a thematic method to explore the meanings of conversations recorded in the Quran.